2020
DOI: 10.3386/w27776
|View full text |Cite
|
Sign up to set email alerts
|

Rugged Individualism and Collective (In)action During the COVID-19 Pandemic

Abstract: We thank Austin Wright for sharing data. All errors are our own. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…In the case of individualism, research has demonstrated that individualist countries implement less stringent measures to combat COVID-19 (Rapson, 2021 ); therefore, undoubtedly leading to less behavioral modifications aimed at curbing the epidemic. Furthermore, according to Bazzi et al ( 2021 ), individualism can undermine prosocial behavior as it is linked to lesser mask usage and social distancing practices. As for indulgence, the hedonistic nature of indulgent cultures might hinder authorities ability to have their citizens respect measures aimed at curbing the COVID-19 crisis (Messner, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of individualism, research has demonstrated that individualist countries implement less stringent measures to combat COVID-19 (Rapson, 2021 ); therefore, undoubtedly leading to less behavioral modifications aimed at curbing the epidemic. Furthermore, according to Bazzi et al ( 2021 ), individualism can undermine prosocial behavior as it is linked to lesser mask usage and social distancing practices. As for indulgence, the hedonistic nature of indulgent cultures might hinder authorities ability to have their citizens respect measures aimed at curbing the COVID-19 crisis (Messner, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Draconian measures should cater to realistic threat but noyt symbolic threat. If anything, in nations with individualistic orientation such as the United States, the use of such measures could conflict with group norms such as anti-statism (Bazzi et al, 2020). In contrast, the relationship between national identity certainty and outgroup conspiracy beliefs should be explained by perceived symbolic but not realistic threat.…”
Section: Covid-19 As Realistic and Symbolic Threatmentioning
confidence: 99%
“…At very least, this disrupts the continuity of an identity (Jaspal & Nerlich, 2020). In some cases, social distancing may even clash with some national norms (e.g., individualism and anti-statism, Bazzi et al, 2020), leaving people uncertain about what defines their nation. In addition, COVID-19 has delivered a heavy blow on global and regional economy (Bartik et al, 2020;Carlsson-Szlezak et al, 2020) and consequently rendered the economic prospect of a nation uncertain.…”
mentioning
confidence: 99%
“…We first address the parallels between sex education and the response to the pandemic by discussing the rugged individualism prized in the United States—a way of relating to self and others that has deep connections to U.S. history, masculinity, and capitalism [ 5 ]. Individualism constitutes an institutionalized set of values that prioritizes autonomy, individual rights, freedom, and choice.…”
Section: Introductionmentioning
confidence: 99%